Pemeriksaan Histopatologi Jaringan Payudara pada Pasien (Carcinoma Mammae) dengan Metode Haematoxylin dan Eosin di Instalasi Patologi Anatomi - Firna, Bismi Rahma (Lembaga Yasin AlSys, 2025)
Histopathological examination plays a crucial role in cancer diagnosis, including carcinoma mammae, yet systematic documentation of technical procedures remains limited, particularly in educational laboratory settings. This study aims to provide a detailed description of the histopathological examination stages of breast tissue using the Hematoxylin and Eosin (HE) staining method in patients with carcinoma mammae. The research employed a descriptive approach conducted at an anatomical pathology laboratory from January to February 2025. The study object consisted of breast tissue specimens from cancer patients, processed through stages including fixation, macroscopic sectioning, dehydration, clearing, impregnation, embedding, microtome sectioning, HE staining, mounting, and microscopic evaluation. Key instruments included a rotary microtome, tissue processor, and autostainer, while materials used comprised alcohol, distilled water, xylol, hematoxylin, and eosin. Results indicate that each procedural step significantly contributes to tissue integrity and the quality of microscopic interpretation. HE staining proved effective in revealing cancer cell morphology, with hematoxylin staining cell nuclei bluish-purple and eosin staining cytoplasm pink. The histological features showed hallmark characteristics of malignant tumor cells, such as nuclear pleomorphism, atypical mitoses, and lymphovascular invasion. In conclusion, the HE staining method enables clear and accurate histological visualization to support the diagnosis of carcinoma mammae.